Growth Behavior of Selected Ustilaginaceae Fungi Used for Mannosylerythritol Lipid (MEL) Biosurfactant Production – Evaluation of a Defined Culture Medium - Beck, Alexander; Zibek, Susanne (Frontiers in Bioengineering and Biotechnology, 2020)
Fungi of the Ustilaginaceae family are a promising source for many biotechnologically relevant products. Among these, mannosylerythritol lipid (MEL) biosurfactants have drawn a special interested over the last decades due to their manifold application possibilities. Nevertheless, there is still a knowledge gap regarding process engineering of MEL production. As an example, no reports on the use of a chemically defined culture medium have been published yet, although such a defined medium might be beneficial for scaling-up the production process toward industrial scale. Our aim therefore was to find a mineral medium that allows fast biomass growth and does not negatively affect the successive MEL production from plant oils. The results showed comparable growth performance between the newly evaluated mineral medium and the established yeast extract medium for all seven investigated Ustilaginaceae species. Final biomass concentrations and specific growth rates of 0.16-0.25 h–1 were similar for the two media. Oxygen demand was generally higher in the mineral medium than in the yeast extract medium. It was shown that high concentrations of vitamins and trace elements were necessary to support the growth. Increasing starting concentrations of the media by a factor of 10 resulted in proportionally increasing final biomass concentrations and up to 2.3-times higher maximum growth rates for all species. However, it could also lead to oxygen limitation and stagnant growth rates when too high medium concentrations were used, which was observed for Ustilago siamensis and Moesziomyces aphidis. Successive MEL production from rapeseed oil was effectively shown for 4 out of 7 organisms when the mineral medium was used for cell growth, and it was even enhanced for two organisms, M. aphidis and Pseudozyma hubeiensis pro tem., as compared to the established yeast extract medium. Conversion of rapeseed oil into MEL was generally improved when higher biomass concentrations were achieved during the initial growth phase, indicating a positive relationship between biomass concentration and MEL production. Overall, this is the first report on the use of a chemically defined mineral medium for the cell growth of Ustilaginaceae fungi and successive MEL production from rapeseed oil, as an alternative to the commonly employed yeast extract medium.